Effect of fluconazole on human polymorphonuclear leucocyte functions ex vivo against Candida albicans - SOYOĞUL GÜRER, ÜMRAN (KARGER, 1999)
Polymorphonuclear leucocytes (PMNs) are important components of host defence against fungi. We investigated the ex vivo effect of fluconazole on chemotaxis, adherence, superoxide anion (O-2(-)) generation and intracellular killing of Candida albicans blastoconidia after the administration of fluconazole (300 mg per os) to healthy volunteers. With regard to chemotaxis in response to zymosan-activated serum (ZAS), as measured using an agarose gel technique, fluconazole neither increased, nor decreased the chemotaxis of PMNs. The adherence was significantly enhanced after exposure of PMNs to fluconazole under ex vivo conditions, whereas, O-2(-) production after stimulation of PMNs with ZAS was not affected by fluconazole. The effect of fluconazole on intracellular killing of C. albicans blastoconidia by PMNs was determined by viable colony count, after release of yeast cells from disturbed neutrophils. Fluconazole under in vitro conditions, at a therapeutic concentration, significantly increased the intracellular killing of C. albicans by PMNs at 30 min when compared with the results obtained in ex vivo experiments (p < 0.001). During 90 min of exposure, no significant difference was found between in vitro and ex vivo conditions (p > 0.05).
Keywords: fluconazole; intracellular killing of Candida albicans blastoconidia; chemotaxis; adherence; superoxide anion generation; HUMAN-NEUTROPHILS; LEUKOCYTES; INVITRO; UK-49,858; KETOCONAZOLE; MONOCYTES; DRUGS